2010
DOI: 10.1148/rg.306105519
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fat at Cardiac Imaging: How Can We Differentiate Pathologic from Physiologic Fatty Infiltration?

Abstract: Myocardial fat is often seen at cardiac computed tomography (CT) and magnetic resonance (MR) imaging of healthy adults and patients with myocardial diseases. Physiologic myocardial fat develops with aging and is commonly seen at CT in the anterolateral right ventricular (RV) free wall and RV outflow tract with normal or thickened RV myocardium and a normal-sized RV in elderly patients. Pathologic conditions with myocardial fat include healed myocardial infarction (MI); arrhythmogenic RV cardiomyopathy or dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 55 publications
(130 reference statements)
2
81
2
1
Order By: Relevance
“…The similar dependence was found in our study-in the group of patients after MI most often fatty foci were localised subendocardially in the LV. A similar dependence was described by Kimura et al [10]. In patients without changes in the coronary arteries, significantly more often fatty deposits were localised within the RV.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The similar dependence was found in our study-in the group of patients after MI most often fatty foci were localised subendocardially in the LV. A similar dependence was described by Kimura et al [10]. In patients without changes in the coronary arteries, significantly more often fatty deposits were localised within the RV.…”
Section: Discussionsupporting
confidence: 83%
“…Physiologic fat is located in the anterolateral RV free wall, RV outflow tract, and sometimes in RV trabeculae and the apex of the heart. In these cases the myocardial wall is either normal or thick [10]. Kirsch et al [11] showed that there is no correlation between the presence of the fat in the RV and the body mass index of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty pattern is associated with preserved myocardial thickness, whereas in the fibrofatty pattern, there is marked thinning of the myocardium (7,17,20,21) (Fig 2). Intramyocardial fat is more commonly seen in the basal and mid free wall, the RVOT, and the lateral apex and occasionally is seen in the inferoseptal portion of the RV, the RV trabeculae, and the moderator band (12,15,22,23). Fibrosis is usually seen in the same place as fat and may result in delayed enhancement after contrast material administration.…”
Section: Other Non-task Force Criteria Findings Of Arvcmentioning
confidence: 99%
“…The presence of myocardial fatty or fibrofatty infiltration is not included in either the revised or the original task force criteria because of (a) artifactual fat resulting from limited imaging techniques (22) and (b) the presence of fatty infiltration in physiologic (20)(21)(22)(23)(24) and other pathologic states, such as healed myocardial infarction (18,(24)(25)(26)(27)(28)(29)(30) (Fig 3), cardiac lipoma (31,32), lipomatous hypertrophy of the interatrial septum (33), tuberous sclerosis complex (34), and dilated cardiomyopathy. Isolated and marked lipomatous infiltration of the RV appears to be a separate condition from ARVC (35).…”
Section: Normal Variants Mischaracterized As Findings Of Arvc Myocardmentioning
confidence: 99%